COURT COSTS IN ECONOMIC PROCEDURAL LAW - Mardonova Aziza Jamolovna (Scholar Express Journals, 2025)
This article presents the concept of court costs, types and rates of court costs, specific features of the collection of state duty by Economic Courts, distribution of court costs and benefits in payment, conditions for the return of state duty. There are also differences between foreign courts.
Keywords: Court costs; state duty; court costs,